Sistem Informasi Geografis untuk Pemetaan Wifi.Id Corner dan Wifi Gratis di Kota Kupang Berbasis Web - Nahak, Paskalis F.; Mamulak, Natalia Magdalena R.; Siki, Yovinia C. H. (Jurnal Teknik Informatika UNIKA Santo Thomas, 2020)
WiFi is a well-known technology that utilizes electronic equipment to exchange data wirelessly (using radio waves) through a computer network, including high speed internet connections. In addition there are currently many internet services for the public provided by companies such as PT. Telkom which provides wifi.id corner and Diskominfo which provides free wifi for public to help people who need internet access for work purposes. In Kupang City Regency,have been many scattered public internet services such as wifi.id corner and free wifi spread, but will there are still many people who do not yet the location information of wifi.id corner and free wifi , so there is a sense of discomfort by people who really need these services. Therefore built a Geographic Information System (GIS) web-based for mapping wifi id corner locations and free wifi using the PHP programming language and MySQL database. This research uses the Waterfall Life Cycle Software Development (CLC) development method. The waterfall model has five stages, namely analysis, design, coding, testing and maintenance. The results of this study are Web-GIS applications that can provide information about Wifi Id Corner and Free Wifi in Kupang City as is of location maps, names, addresses, facilities and images wifi id corner locations and the selected free wifi locations.